Don Vicente two novels - José, F. Sionil (Francisco Sionil) 1924-; Jose, Francisco Sionil 1924-; Jose, Francisco Sionil 1924- (New York Modern Library, 1999)
A novel on the Huk rebellion in the Philippines early this century, featuring a man who joins a peasant revolt against his father, a feudal landlord. The revolutionary attempts to persuade his half-brother to join, but the other refuses.
Tree -- My brother, my executioner.
Originally published in English as Tree and My Brother, My Executioner by Solidaridad Pub. House, Manila.
Tac-3294g donated by Eloisa and Anthony Quiambao on August 26, 2021.
Keywords: Philippines -- History -- Fiction